2015
DOI: 10.2340/00015555-1911
|View full text |Cite
|
Sign up to set email alerts
|

Course of Skin Symptoms and Quality of Life in Children Referred for Patch Testing – A Long-term Follow-up Study

Abstract: Children are patch tested in the same manner as adults, but little has been done to establish whether positive or negative findings influence the course of skin symptoms. To uncover the course of skin symptoms and the impact of persistent eczema on life quality in paediatric patients referred for patch testing, a retrospective questionnaire was sent to children and adolescents referred for patch testing during a 9-year period. Persistent eczema at follow-up was strongly associated to atopic dermatitis, but was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
1
9
2
Order By: Relevance
“…High scores of the item on ‘restrictions and limitations’ in children with ACD and AD are a result of the so-called avoiding strategy. Difficulties in adopting suitable avoidance behaviour by patients who were diagnosed with ACD is a well-known problem [ 24 ]. Therefore a high score for ‘restrictions and limitations’ in children with ACD may reflect an adequate avoiding strategy provided by their parents.…”
Section: Discussionmentioning
confidence: 99%
“…High scores of the item on ‘restrictions and limitations’ in children with ACD and AD are a result of the so-called avoiding strategy. Difficulties in adopting suitable avoidance behaviour by patients who were diagnosed with ACD is a well-known problem [ 24 ]. Therefore a high score for ‘restrictions and limitations’ in children with ACD may reflect an adequate avoiding strategy provided by their parents.…”
Section: Discussionmentioning
confidence: 99%
“…Children with ACD have worsened quality of life measures such as reduced sleep quality, impaired school performance, and problems with friends or relatives. 136 Younger children with ACD were found to have lower occupational and functional quality of life scores compared to older children. 137 Validated ACD-specific questionnaires have shown that the emotional aspect of the disease is most burdensome, a measure that improved months after allergen avoidance.…”
Section: Quality Of Lifementioning
confidence: 97%
“…All but one of these modifications extended the 1-week recall period of the original DLQI. Of these, LY-DLQI was the most common by having been used in 7 independent studies, 43,[79][80][81][82][83][84] and another 2 studies (4 publications) 45,[85][86][87] applied a 1-year recall period along with other modifications made. The LY-DLQI allows to capture the long-term HRQoL impact of skin diseases as well as to compare scores with those of the original DLQI.…”
Section: Discussionmentioning
confidence: 99%